MOBILE LEARNING VOCAPP: (VOCABULARY APPLICATION) FOR ENGLISH VOCABULARY LEARNING - Badroeni Badroeni; Sofhian Fazrin Nasrulloh; Oman Suryaman (University of Kuningan, 2022)
The background of this research is to investigate the urgency of vocabulary as the most important aspect in language. In this research, vocabulary learning will be assisted by using an android application, namely VocApp; (Vocabulary Application). The purpose of this research and development is to (1) identify the needs of vocabulary learning media according to teachers and students, (2) know the principles of developing learning media based on theoretical studies, identify needs and analyze existing learning media, (3) design VocApp learning media based on the results of the analysis of the existing media, (4) test the VocApp learning media (5) Revise the features of the application according to the evaluation of the trial, (6) Disseminate and implement applications for vocabulary learning in the classroom. The method used is research and development. The steps in the research are Needs analysis, Prototyping, Revision Prototype, Developing, Testing, and Deployment. The result indicated there is a significant improvement of students’ skill in vocabulary building by means of VocApp application. This case can be seen from the results of calculations using statistical tools, it is known that t-count is 0.03 which means <0.05. From the results of t-count, it can be concluded that there is a significant difference.